Predictors of postoperative mortality among neonates after major-risk surgery: A one-year experience from a Tunisian hospital - Manel Kammoun; Anouar jarraya; Hechem bradai; Hind ketata; Hasna Bouchaira; Olfa Cherif; Amel Ben Hamed; Faiza Safi; Riadh Mhiri (EL-Med-Pub, 2023)
Background: Neonatal surgery in developing countries remains a high-risk modality p and its outcomes depend on various patient-related, system-related, and management-related factors. This study aims to describe our experience in managing newborns requiring surgical interventions and to investigate the primary predictors of postoperative mortality. Methods: In this observational study, we included all newborns aged less than 28 days who underwent surgery in the pediatric surgery department under general anesthesia with tracheal intubation for major-risk surgery. Patients were categorized into two groups based on the outcome (survival or death) during the two months following surgery. Following a comparison of the two groups, univariable and multivariable logistic regression analyses were conducted to explore predictors of perioperative mortality among neonates. Results: Sixty-seven newborns were included in this study, with an early mortality incidence of 28.3%. Anesthesia management did not impact neonatal mortality. The main predictors of neonatal mortality were revision surgery [aOR=35.5; 95% CI: 1.33- 94.1], surgery duration ≥ 120 minutes [aOR=36.5; 95% CI: 1.48- 312], preoperative mechanical ventilation [aOR=3.88; 95% CI: 1.12- 30.8], and the occurrence of perioperative adverse events [aOR=5.7; 95% CI: 1-29.5] or postoperative surgical complications [aOR=32.5; 95% CI: 1.05-101]. Conclusion: The early mortality rate after major neonatal surgery remains high in our department. It appears that preoperative poor conditions can elevate the risk. Additionally, major-risk surgeries requiring prolonged procedures and revision surgery, along with the incidence of postoperative infections, significantly increase the risk of neonatal mortality.